2020
DOI: 10.2196/16045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankle Plantar Flexor Spasticity Level on Balance in Patients With Stroke: Protocol for a Cross-Sectional Study

Abstract: Background The lower limb spasticity after stroke can affect the balance and gait of patients with stroke. Objective The aim of this study is to assess the effects of ankle plantar flexor spasticity level on balance in patients with stroke. Methods Patients with stroke were recruited from neurology and physiotherapy clinics in Tehran, Iran. Based on the level of ankle plantar flexor spasticity according to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The protocol of this cross-sectional study has been previously reported ( Mahmoudzadeh et al, 2020 ) with the exception of one modification made on posturography. The present study utilized two force plates to assess the both affected and less affected limbs separately.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol of this cross-sectional study has been previously reported ( Mahmoudzadeh et al, 2020 ) with the exception of one modification made on posturography. The present study utilized two force plates to assess the both affected and less affected limbs separately.…”
Section: Methodsmentioning
confidence: 99%
“…Considering a previous study and β = Z β = 0.842, α = 0.05, α = Z α = 1.96 ( Rahimzadeh Khiabani et al, 2017 ; Mahmoudzadeh et al, 2020 ), the sample size was calculated at 28 ( n = 14 in each group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Stroke survivors present with several clinical manifestations, such as muscle weakness, spasticity, neglect, cognitive dysfunction, and physical limitations. [ 1 - 3 ] Balance ability and knee extensor strength are strong predictors of walking ability in subacute stroke. [ 4 , 5 ] To date, the isokinetic assessment is the gold standard method for measuring muscle strength after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ankle plantarflexor spasticity demonstrate greater gait and balance dysfunction compared to those without this distribution of spasticity [ 18 , 19 , 20 , 21 ]. The MTS assessment is often used to measure ankle plantarflexor spasticity and guide treatment planning, but as discussed, the use of IMUs to measure spasticity in adults with plantarflexor spasticity is not well reported.…”
Section: Introductionmentioning
confidence: 99%